Farmers’ Interest and Economics Model of Agrosilvofishery Restoration on Degraded Peatland in OKI Regency South Sumatra Indonesia - ema, Ema pusvita; Mulyana, Andy; Adriani, Dessy; Antoni, Mirza (Journal of Smart Agriculture and Environmental Technology, 2023)
The sustainability of peatlands required sustainable thinking to protect the existing ecosystem. One of the restoration efforts was the application agrosilvofishery model with 3R (Rewetting, Revegetation and Revitalization) on peatlands. The research objective was to examine the economic value of application agrosilvofishery model on peatlands with a combination of jelutung, chilies and catfish. The research method used purposive sampling method where research location was selected in OKI Regency, South Sumatra. The sample of research was 10 who has their own degraded peatlands, then empowerment them to cultivate peatlands, to obtain the optimal benefits. It was selected based on quota in action research. Farmers selected forest and fruit plants to plant on peat based on their interests. In economic study, the acceptance value was obtained from the agrosilvofishery model, namely jelutung Rp. 716,473,469/m3/30 years, jelutung sap 2,782,080,000/kg/30 years, chilies received Rp. 40,000,000/year, and the average income for catfish was Rp. 1,836,000,000/year. Sensitivity analysis of jelutung-chili-catfish agrosilvofishery obtained an NPV of Rp. 13,413,797,049, IRR (+) 60%, Net B/C 7.1, Gross B/C 3.7, and PP 0.01/year. From the results of this study, farming on peatland with the agrosilvofishery model was feasible. The development strategy by using the business canvas model agrosilvofishery provided an overview of peatlands sustainability in future. Further, this research provided an illustration that to provide for a decent life, farmers need to think about short, medium and long term businesses.   Keywords: Agrosilvofishery, Chili, Jelutung, Catfish, Canvas Business